IMPLEMENTASI APLIKASI BEBUNGE SEBAGAI UPAYA PENINGKATAN PELAYANAN DI KABUPATEN BEKASI - Hadiansyah Wisnu Widodo; Muhammad Fadil (Governance, 2022)
The Bebunge application is a facility provided by the Bekasi Regency government to make it easier for the public to obtain information, convey aspirations and complaints, and obtain public services in Bekasi Regency. The purpose of this study was to determine the implications of the bebunge application in developing innovation in Bekasi Regency. The research method used is qualitative research with the results of data processing with data collection techniques through direct interviews, documentation and observation. In this study, the theory of the application of e-government is used, namely the theory includes indicators such as Content Development, Competency Building, Connectivity, Cyber ​​Laws, Citizen Interfaces and Capital. The results of the research show that the application of the Bebunge Application in Bekasi Regency in terms of socialization to the community is still lacking, because socialization is only through digital media such as Twitter, Instagram, or Youtube. So that the user community still does not understand much about the application of the Bebunge application in Bekasi Regency. The conclusion in this study is that in the implementation of the Bebunge application in developing innovations in the field of information technology in Bekasi Regency, it is not optimal, it is seen from the side of socialization to the community directly.